Role of NADPH Oxidase-Induced Hypoxia-Induced Factor-1α Increase in Blood-Brain Barrier Disruption after 2-Hour Focal Ischemic Stroke in Rat. (16th August 2021) - Wang, Yanping; Shen, Yufei; Yu, Xin; Gu, Jingxia; Zhang, Xiaoling; Zhou, Beiqun; Sun, Yanyun; Xu, Congying; Qian, Shuxia
Abstract : We recently showed that inhibition of hypoxia-induced factor-1 α (HIF-1 α ) decreased acute ischemic stroke-induced blood-brain barrier (BBB) damage. However, factors that induce the upregulation of HIF-1 α expression remain unclear. Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase played a critical role in reperfusion-induced BBB damage after stroke. However, the role of NADPH oxidase in BBB injury during the acute ischemia stage remains unclear. This study is aimed at investigating the role of NADPH oxidase in BBB injury and the expression of HIF-1 α after acute ischemic stroke. A sutured middle cerebral artery occlusion (MCAO) model was used to mimic ischemic stroke in rats. Our results show that the inhibition of NADPH oxidase by apocynin can significantly reduce the BBB damage caused by 2 h ischemic stroke accompanied by reducing the degradation of tight junction protein occludin. In addition, treatment with apocynin significantly decreased the upregulation of HIF-1 α induced by 2 h MCAO. More importantly, apocynin could also inhibit the MMP-2 upregulation. Of note, HIF-1 α was not colocalized with a bigger blood vessel. Taken together, our results showed that inhibition of NADPH oxidase-mediated HIF-1 α upregulation reduced BBB damage accompanied by downregulating MMP-2 expression and occludin degradation after 2 h ischemia stroke. These results explored the mechanism of BBB damage after acute ischemic stroke and may help reduce the associated cerebral hemorrhage transformation after thrombolysis and endovascular treatment after ischemic stroke.